2022
DOI: 10.1177/08982643221081965
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Mental Health and Well-Being between Heterosexual and Sexual Minority Older Adults during the COVID-19 Pandemic

Abstract: Objectives: This study examines disparities in older adults’ mental health and well-being during the pandemic by sexual minority status. Methods: This study analyzed data on older adults from the Health and Retirement Study’s COVID-19 Module (N = 3142 for heterosexuals and N = 75 for sexual minorities). Weighted regressions linked concern about COVID-19, depression, pandemic emotional stress, and changes in loneliness, in-person contacts, income, and work to sexual minority status, controlling for sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…According to the findings of the present study, participants aged 50 years old or older were more likely to report minimal to moderately severe depressive symptoms compared to all other age groups. This aligns with previous literature that has found that older LGBTQ individuals were more likely to report emotional distress than non-LGBTQ people during the pandemic [49]. Increased attention to the needs of older LGBTQ individuals, especially during times of national and global emergency, is warranted, as this group is generally more vulnerable, having experienced decades of stigma, criminalization, discrimination, grief, victimization, and social and economic exclusion [50].…”
Section: Discussionsupporting
confidence: 87%
“…According to the findings of the present study, participants aged 50 years old or older were more likely to report minimal to moderately severe depressive symptoms compared to all other age groups. This aligns with previous literature that has found that older LGBTQ individuals were more likely to report emotional distress than non-LGBTQ people during the pandemic [49]. Increased attention to the needs of older LGBTQ individuals, especially during times of national and global emergency, is warranted, as this group is generally more vulnerable, having experienced decades of stigma, criminalization, discrimination, grief, victimization, and social and economic exclusion [50].…”
Section: Discussionsupporting
confidence: 87%
“…For the next phase of our research, we plan to utilize topic modeling methods, such as BERTopic [64], to generate topic clusters and automatically extract frequently occurring words to represent the topic of each cluster. Additionally, we plan to combine the current text analysis method with existing data gathered through interviews and survey results, such as the 2020 Health and Retirement Survey (HRS) [36], to better understand and categorize LGBTQ+ elders' resilience during the COVID-19 pandemic. We hope that this will further demonstrate the potential of using such mixed methods to uncover other aspects of strengthened resilience that were previously overlooked, and thereby inform future decisions in policy-making and healthcare and health information service provision, as well as promote additional community networking and other internal support mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The unique experiences of LGBTQ+ elders during COVID-19 have primarily been studied to date through interviews and surveys, which can have important logistical limitations in the scope and number or type of participants [36]. With the aim of expanding the scope and methods of such research as well as exploring online information-seeking behavior and queries of LGBTQ+ elders, our study takes a different approach and applies computational discourse analysis to the results of online searches for health information for this population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 25 The COVID-19 pandemic often has been described as a “perfect storm” of multiple sources of stress and has been linked to worsened mental health and health behaviors overall. 21 , 22 , 26 29 There is evidence of increased problematic alcohol use during previous pandemics; 30 however, the COVID-19 pandemic is unique among recent pandemics in the breadth and duration of its impacts and thus may have more substantial effects on health and well-being, including alcohol use. Cisgender women, compared to cisgender men, may be particularly affected by the pandemic due to higher levels of stressors.…”
mentioning
confidence: 99%